Kesehatan Reproduksi Pada Remaja Di Era Pandemi Covid-19 - Maria Haryanti Butarbutar; Sri Lasmawanti; Ani Deswita Chaniago; Rupina Situmorang (Insight Power (Kekuatan Wawasan), 2022)
WHO said that adolescents are in the age range of 10-19 years, and in accordance with the regulation of the Minister of Health of the Republic of Indonesia Number 25 of 2014, said that adolescents are in the age range of 10-18 years and according to the Population and Family Planning Agency (BKKBN) the age range Teenagers are 10-24 years old and unmarried. Adolescence is a period with an age range of 10 to 24 years which is a transitional phase from childhood (dependent) to adulthood (independent) and normally occurs in human life. During this period, a teenager will experience a lot of development and growth in order to find his identity and identity. Various changes will appear both from the psychological, physical (puberty), and social environment. The purpose of community service is to prevent the occurrence of free sex for adolescents, adolescents know the growth and development of the transition period, prevent sexually transmitted diseases, norms, and ethics of Indonesian life. The method uses the Participatory Learning and Action (PLA) approach. The participants of the training activity were 35 students from Class XI SMA Private High School Amanah Tahfidz Deli Serdang. The activity was carried out on January 17, 2022. The implementation is divided into several stages, namely (1) the pre-activity stage, (2) the activity implementation stage, and (3) the evaluation stage. The development stage includes analysis, design, implementation, and testing. Reproductive health education using leaflets and stories. The activities carried out were expected to make class XI students of Amanah Tahfidz Deli Serdang Private High School more understand about reproductive health in adolescents and were closely related to preventing sex in adolescence in the pandemic era.Keywords: Community Service, Reproductive Health, Youth